2016
DOI: 10.1111/iej.12672
|View full text |Cite
|
Sign up to set email alerts
|

Expression of KLF5 in odontoblastic differentiation of dental pulp cells during in vitro odontoblastic induction and in vivo dental repair

Abstract: KLF5 might be involved in the process of odontoblastic differentiation during reparative dentine formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 25 publications
(57 reference statements)
1
16
0
Order By: Relevance
“…Specifically, Liu et al [] performed miRNA‐profiling assays of mouse odontoblast differentiation and revealed that the knockdown of miR‐143 promoted odontoblast differentiation both in vivo and in vitro. Several studies revealed that ALP activity was significantly decreased during odontoblastic differentiation [Kim et al, ; Han et al, ; Woo et al, ]. Furthermore, the suppression of DPSC odontoblast differentiation also led to fewer mineralized nodules [Rao et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Liu et al [] performed miRNA‐profiling assays of mouse odontoblast differentiation and revealed that the knockdown of miR‐143 promoted odontoblast differentiation both in vivo and in vitro. Several studies revealed that ALP activity was significantly decreased during odontoblastic differentiation [Kim et al, ; Han et al, ; Woo et al, ]. Furthermore, the suppression of DPSC odontoblast differentiation also led to fewer mineralized nodules [Rao et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, iMDP-3 cells were grown in differentiation medium, and the mRNA level of Dspp and Dmp1 was upregulated during odontoblastic induction. These results were consistent with our previous observation 25 . Similar to Dspp and Dmp1, Klf5 expression was gradually upregulated in mouse dental papilla mesenchymal cell differentiation and mineralization.…”
Section: Discussionsupporting
confidence: 94%
“…In addition, in reparative dentine formation study, Klf5 was expressed in the odontoblast-like cells and DPCs beneath the perforation sites. These data indicate Klf5 participates in odontoblastic differentiation and reparative dentine formation25. Although Klf5 plays dual biological roles in cell proliferation, differentiation and migration via regulation of its target genes234525, the role of Klf5 in odontoblastic differentiation is still not clear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations